Stellaria media (L.) Vill.- A plant with immense therapeutic potentials: phytochemistry and pharmacology. Issue 6 (June 2020) - Oladeji, Oluwole Solomon; Oyebamiji, Abel Kolawole
Abstract: Stellaria media Vill. is a representative of Caryophyllaceae family. The plant is widely dispersed all over the world and has been used as therapeutic substance since time immemorial. This review is aimed at exploring the chemical constituents and pharmacological activities of S. media . The findings revealed important secondary metabolites such as flavonoid, oligosaccharide stellariose, anthraquinone derivatives, fatty acid, steroid saponins and phenolic compounds. These bioactive metabolites displayed diverse pharmacological activities such as anti-obesity, antifungal, antibacterial, antioxidant, anti-proliferative, anti-inflammatory, analgesic, antidiabetic and anxiolytic activities. All findings revealed that S. media is a major species of Caryophyllaceae family. However, bioactive constituents and pharmacological potential of are not well appraised. Hence, extracts with established pharmacological activities should be subjected to bioassay guided isolation so as to obtain compounds with novel structural moieties prior to toxicogenetic appraisals. Abstract : Stellaria media ; Caryophyllaceae; ethnopharmacological, phytochemistry; biological activities; Plant Biology; Pharmaceutical Science; Biochemistry; Pharmacology; Evidence-Based Medicine